Pinocho en Amerindia - Vasconez, Miranda (Revista Universidad de Guayaquil, 1998)
Pinocchio eventually convinced poor Gepetto of the need to travel to brown America.—Well, but there: see, hear, and study!... initially; then, we'll see.—I promise you.They arrived in a city that had a small airport, some mosquitoes crossed with woodpeckers, and very special people, a strange cocktail of solidarity and delinquency.